Clinical Profile of Snake Bite Envenomation in Patients Admitted at Tertiary Care Hospital (Academia Journal of Medicine, 2019)
Background: Snakebite envenoming is a potentially life-threatening disease that typically results from the injection of venom following the  bite of a venomous snake. Sometimes envenoming can also be caused by venom being sprayed into a person’s eyes by certain species of  snakes that have the ability to spit venom as a defense measure. Not all snakebites are venomous. Some snakes are non-venomous and  venomous snakes do not always inject venom during a bite. Subjects and Methods: Patients were examined for complications of snake bite.  Haemotoxicity was assessed based on features like bleeding from the bite site, gums, epistaxis, haemoptysis, haematemesis, rectal bleeding or  malaena, haematuria, vaginal bleeding, bleeding into the mucosae, skin (petechiae, purpura, discoid haemorrhages, ecchymoses. Neurotoxicity  by drowsiness, paraesthesiae, abnormalities of taste and smell, ptosis, external ophthalmoplegia, paralysis of facial muscles and other muscles  innervated by the cranial nerves, respiratory and generalized flaccid paralysis. Results: Majority of the patients were farmers with 44%  followed by housewives (26%). Lower limbs were the most common site of bite in our study group comprising of74% of the patients. Conclusion: Most common manifestation of envenomation is local envenomation comprising of 66%.
Keywords: Snake Bite Envenomation; Haemotoxicity; Neurotoxicity